SPEECH THERAPY IN THE THERASUIT METHOD: INNOVATIONS AND CONTRIBUTIONS IN CHILD REHABILITATION - Cavalcanti Bernardo Guedes, Cecília (Health and Society, 2023)
The research deals with the benefits of the Therasuit method and its speech therapy contributions. As it was inaugural in speech therapy through obtaining certification to work in the area, we present important results for greater visibility in the use of the Intensive Speech program in Therasuit IFT. This is a case-study type research with treatment of qualitative and quantitative data collected from filming and analyzed according to the rigor of the recorded method of rehabilitative stimulation. The results show a conclusive contribution of the method in speech therapy capable of offering the patient with speech motor disorders promotion of global aspects of speech and language in children.